ANALISIS TENTANG PERUBAHAN MAKNA NILAI DALAM TRADISI MUSIK BARDAH DI KAMPUNG BUATAN II KECAMATAN KOTO GASIB KABUPATEN SIAK - Mutia Loka; Hambali Hambali; Zahirman Zahirman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract:This research is motivated by changes in the meaning of values in the Bardah music tradition. where there are changes in the tradition of bardah music in ancient times and today.the formulation of this research problem is“what aspects have changed in the bardah music tradition in the second village made in koto gasib district of siak district and what factors influence changes in the meaning of the value of the bardah music tradition in the second artificial village in the koto gasib district of siak district. the purpose of this research is“to find out what aspects have changed in the tradition of bardah music in the artificial village II of the KotoGasib district of Siak Regencyand to find out what factors influence changes in the meaning of the value of the Bardah music tradition in the artificial village II of the Koto Gasib district of Siak Regency , practically the results of this research are expected to increase knowledge for readers and increase knowledge for the researchers themselves.Data collection techniques are observation, interview, and documentation. Respondents in this study were taking 10 simple people, 4 of whom were bardah musical instruments players. Data analysis techniques in this study used qualitative methods.the results of this study are: where found changes in the tradition of bardah music, these changes include